2000
DOI: 10.1080/07053436.2000.10715606
|View full text |Cite
|
Sign up to set email alerts
|

A View of Leisure and Patterns of Family Life in the Late 1990s

Abstract: During the last two decades, feminist analysis has brought to light the structural factors circumscribing women's leisure such as age,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Feminist sociology challenged the normative notion of the nuclear family (Smith, 1993) and contemporary family sociology recognises diversity in family life (Chambers, 2012;Hill, 2012). Family leisure researchers also acknowledge the influence of ethnic, racial, religious, class and sexual identities on family life and leisure (Bialeschki & Pearce, 1997;Rehman, 2001;Shaw & Dawson, 1998;Willming & Gibson, 2000), but have not really explored how diverse families practice and value family leisure. Shaw (2010) discussed implications of diversity in Canadian families for both family leisure and personal leisure and the tensions between them, but the empirical work remains to be done.…”
Section: Introductionmentioning
confidence: 96%
“…Feminist sociology challenged the normative notion of the nuclear family (Smith, 1993) and contemporary family sociology recognises diversity in family life (Chambers, 2012;Hill, 2012). Family leisure researchers also acknowledge the influence of ethnic, racial, religious, class and sexual identities on family life and leisure (Bialeschki & Pearce, 1997;Rehman, 2001;Shaw & Dawson, 1998;Willming & Gibson, 2000), but have not really explored how diverse families practice and value family leisure. Shaw (2010) discussed implications of diversity in Canadian families for both family leisure and personal leisure and the tensions between them, but the empirical work remains to be done.…”
Section: Introductionmentioning
confidence: 96%
“…However, PA can also be higher in case when children mobilize parents to active spending of free time 31 , 32 or when parents motivate themselves when children move away from a family home. 33 …”
Section: Introductionmentioning
confidence: 99%
“…Reflecting the findings of other research (Willming & Gibson, 2000), the onset of parenthood has been shown to crucially alter both men's and women's leisure. Analysis of men's leisure throughout the lifecourse revealed that transitions to the fatherhood role were accompanied with a loss of the amount of autonomy and freedom fathers could exercise over their leisure time and leisure choices.…”
Section: Discussionmentioning
confidence: 90%
“…Macro changes in both the structure of family-employment life and in particular the decline in the male-breadwinner family required leisure theorists to reassess the relationship between fatherhood and leisure from the 1980s. In addition the emergence of a 'second-wave feminism' called into question the andocentric evolution of male-dominated theoretical approaches to leisure (Willming & Gibson, 2000). These combined factors served to stimulate a re-examination of the work-leisure dichotomy.…”
Section: Fathers In Leisure Studiesmentioning
confidence: 98%